The Concept of Loyalty in Kenneth Graham’s The Wind in the Willows - Instructor Mr. Maytham Ali Khalefa (Periodica Journal, 2022)
The Wind in the Willows 1908, is one of Graham’s greatest works of fiction. Many people also perceive it as one of children’s literature masterpieces ever written. Writers and scholars alike have addressed a wider range of concepts and issues in the novel. The novel maintains its popularity and appeal due to the enduring nature of the ideas and themes it seemingly never ceases to offer. It has replenished its readers with an uninterrupted variety of themes and subjects that would range from friendship to family, and from class to pastoral world. However, the concept of loyalty in the novel seems to be unaddressed thus far. Therefore, the current research paper is intended to explore and investigate this particular concept of loyalty in the novel assuming that it runs throughout the novel as demonstrated by its characters and the various events related to them
Keywords: Literature; Friendship; Loyalty; Animals